The influence of fellowship training on the practice of pancreatoduodenectomy. Issue 12 (December 2016) - Kennedy, Gregory T.; McMillan, Matthew T.; Sprys, Michael H.; Bassi, Claudio; Greig, Paul D.; Hansen, Paul D.; Jeyarajah, Dhiresh R.; Kent, Tara S.; Malleo, Giuseppe; Marchegiani, Giovanni; Minter, Rebecca M.; Vollmer, Charles M.
Abstract: Background: There has been a proliferation of gastrointestinal surgical fellowships; however, little is known regarding their association with surgical volume and management approaches. Methods: Surveys were distributed to members of GI surgical societies. Responses were evaluated to define relationships between fellowship training and surgical practice with pancreatoduodenectomy (PD). Results: Surveys were completed by 889 surgeons, 84.1% of whom had completed fellowship training. Fellowship completion was associated with a primarily HPB or surgical oncology-focused practice ( p < 0.001), and greater median annual PD volume ( p = 0.030). Transplant and HPB fellowship-trained respondents were more likely to have high-volume (≥20) annual practice ( p = 0.005 and 0.029, respectively). Regarding putative fistula mitigation strategies, HPB-trained surgeons were more likely to use stents, biologic sealants, and autologous tissue patches ( p = 0.007, <0.001 and 0.001, respectively). Surgical oncology trainees reported greater autologous patch use ( p = 0.003). HPB fellowship-trained surgeons were less likely to routinely use intraperitoneal drainage ( p = 0.036) but more likely to utilize early (POD ≤ 3) drain amylase values to guide removal ( p < 0.001). Finally, HPB fellowship-trained surgeons were more likely to use the Fistula Risk Score in their practice (29 vs. 21%, p = 0.008). Conclusion: Fellowship training correlated with significant differences in surgeon experience, operative approach, and use of available fistula mitigation strategies for PD.